1991
DOI: 10.1161/01.atv.11.3.770
|View full text |Cite
|
Sign up to set email alerts
|

Effects of serotonin-receptor blockade on angioplasty-induced vasospasm in an atherosclerotic rabbit model.

Abstract: Vasospasm occurs both in patients and animal models after angioplasty and may be associated with early closure of the dilated vessel. To investigate the mechanism of angioplasty-induced vasospasm, the effect of serotonin-receptor blockade with two serotonin? (SJ antagonists, LY53857 and sergolexole, was examined in rabbits with focal femoral artery atherosclerosis. In preliminary studies, local infusion of 1-100 /ig serotonin caused significant femoral artery vasoconstriction (p<0.05) in both normal and athero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…In systemic arterial smooth muscle, 5-HT induces contractions only at sites of endothelial damage where platelet aggregation occurs, and this effect is antagonized by 5-HT 2 receptor antagonists (Sigal et al, 1991). Serotonin also amplifies the effects of other vasoconstrictors, such as histamine, angiotensin II, prostaglandin F 2 , and noradrenaline (O'Rourke et al, 2006).…”
Section: Vasoconstrictionmentioning
confidence: 99%
See 1 more Smart Citation
“…In systemic arterial smooth muscle, 5-HT induces contractions only at sites of endothelial damage where platelet aggregation occurs, and this effect is antagonized by 5-HT 2 receptor antagonists (Sigal et al, 1991). Serotonin also amplifies the effects of other vasoconstrictors, such as histamine, angiotensin II, prostaglandin F 2 , and noradrenaline (O'Rourke et al, 2006).…”
Section: Vasoconstrictionmentioning
confidence: 99%
“…Functional analyses of the roles of 5-HT in the cardiovascular system using 5-HT 2A receptor knockout mice have not been performed. Several studies performed before the discovery of specific and/or selective 5-HT 2A receptor antagonists indicated that 5-HT 2 receptor blockers inhibit angioplasty-induced vasospasm and microvascular constriction following atherosclerotic plaque rupture in atherosclerotic rabbit models (Sigal et al, 1991;Taylor et al, 2004).…”
Section: -Ht 2a Receptor Blockadementioning
confidence: 99%
“…After balloon angioplasty of atherosclerotic femoral arteries in rabbits, coronary spasm occurs that is prevented by serotonin antagonists. 42 High concentrations of serotonin have been measured in the coronary sinus following angioplasty in patients with atherosclerotic coronary artery lesions. 43 Therefore, angioplasty and other acute vascular events appear to release serotonin from platelets that may reach concentrations in local vascular tissue comparable to those used in our in vitro experiments.…”
Section: Dependence Of Platelet-induced Smc Proliferation On Peptide mentioning
confidence: 99%
“…Ten micrograms of serotonin, a dose previously shown to produce significant vasoconstriction, was given as a bolus injection through the catheter. 22 Angiography was repeated 5 minutes later to assess the effect of the infusion on angiographic luminal diameter. Angiography was repeated 45 minutes after administration of the serotonin to confirm that angiographic dimensions had returned to baseline.…”
Section: Effect Of Fluoxetine On Serotonin-mediated Vasoconstrictionmentioning
confidence: 99%
“…receptor antagonists can prevent angioplasty-induced vasospasm both proximal and distal to the treated site. 22 This suggests that serotonin released from activated platelets at the site of balloon angioplasty may be an important mediator of angioplasty-induced vasospasm.…”
mentioning
confidence: 99%